Trajectories of family and employment stress associated with cerebrovascular accidents - Jerez Ríos, María Pilar; Madero-Cabib, Ignacio (Revista de Saúde Pública, 2021)
OBJECTIVES: Reconstruct types of simultaneous stress trajectories in the family and employment domain at different stages of life and estimate their association with cerebrovascular accident (CVA) in old age. METHODS: We used a retrospective, face-to-face, representative survey of people aged 65 to 75 years in the city of Santiago, Chile, (n = 802). We performed a multichannel sequence analysis to reconstruct family and employment stress trajectory types at various life stages and then used logistic regression models to estimate the association of these trajectory types with CVA in old age, controlled for traditional cardiovascular risk factors. RESULTS: Four representative types of family and employment stress trajectories were identified: (1) Absence of family and employment stress, (2) Absence of family stress, persistent employment stress, (3) Absence of family stress, out of the labor market, and (4) Persistent family stress, absence of employment stress. The 61.7% of the sample followed trajectories marked by the permanent presence of family and/or employment stress. Likewise, 18.3% had a trajectory characterized by prolonged absence from the labor market. Individuals with persistent family or employment stress trajectories, as well as those with extended periods of inactivity, are more at risk of developing CVA. CONCLUSIONS: Stress is a risk factor for cardiovascular disease experienced by many people at different stages and domains of life on a prolonged basis. Consequently, prevention systems for this type of chronic diseases should emphasize the highly harmful effects of daily and cumulatively stressful life experiences. This could mitigate the multiple health and financial consequences associated with CVA.